Analisis Dampak Penggunaan Teknologi Informasi Komunikasi Dalam Meningkatkan Minat Belajar Siswa Di Sdn Jatra Timur - Abdur Rofik; Sri Agustini; Supriatin; Miftachul Jannah; Iva Faizah (Journal Educatione, 2025)
The rapid development of information and communication technology, particularly in education, demands that teachers and students be responsive and active in its use. This study aims to analyze the impact of Information and Communication Technology (ICT) use on increasing student learning interest at SDN Jatra Timur. The development of ICT has brought significant changes to the education sector, providing new opportunities for learning implementation, such as simplifying material delivery, helping students master concepts, and honing their technological skills. This study used a qualitative method with a field research approach, conducted at SDN Jatra Timur. The results showed that the implementation of ICT at SDN Jatra Timur, although limited to media, resources, and evaluation, has had a positive and significant impact on increasing students' interest in learning. ICT functions as a learning aid and integrated discipline across all subjects, in accordance with the demands of the Independent Curriculum. Students demonstrate greater enthusiasm and perceive ICT-based learning (e.g., using LCD projectors and the internet) as more modern and engaging, ultimately enhancing their enthusiasm for learning. Students exhibit a strong interest in learning, such as actively asking questions, diligently completing assignments, and enjoying independently problem-solving. However, several obstacles remain, including limited infrastructure (lack of computers and projectors), limited teacher and student skills and motivation, and limited teacher preparation time. To address these challenges, it is recommended to regularly intensify ICT training for teachers and students, and prioritize the provision of adequate facilities. With this optimization, it is hoped that the quality of learning will continue to improve, and students will be increasingly prepared to face the challenges of the digital world.